Diagenetic history of the Chuping Limestone at Bukit Tungku Lembu, Perlis, Malaysia - Noorhashima Adenan,; Che Aziz Ali,; Kamal Roslan Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2017)
The Early Permian to Late Triassic limestone of Chuping Formation in Bukit Tungku Lembu consists of six microfacies and exhibits various types of diagenetic products, reflecting it’s complicated diagenetic history. Out of 89 samples collected for petrographic studies, six major microfacies have been identified, namely brecciated limestone, dolomites, mudstones, wackestones, packstones and grainstones. Four major diagenetic processes comprising micritization, cementation, compaction and dolomitization have also been identified. Micritization occurs as the first phase diagenesis after the sediments were deposited on the sea floor, followed by cementation in the marine environment and also in meteoric environments when the shallow marine carbonate at some points in time was subjected to subaerial exposure. Early burial were indicated by fractures and deformation as well as destruction of grains whole structure. Increasing pressure during deeper burial has produced dissolution seams and stylolites. Dolomitization also occurred in the deeper burial environments.